Second Hankel Determinant for Analytic Functions Defined by Ruscheweyh Derivative - T. Yavuz (International Journal of Analysis and Applications, 2015)
Let S denote the class of analytic and univalent functions in the open unit disk D= {z:|z|<1} with the normalization conditions. In the present article an upper bound for the second Hankel determinant |a₂a₄-a₃²| is obtained for the analytic functions defined by Ruscheweyh derivative.